A theoretical analysis of welded steel joints in rectangular hollow sections - Packer, Jeffrey A. (1978)
In this thesis a theoretical analysis is presented for statically loaded structural hollow section (SiuS) lattice girder joints having one compression bracing member and one tension bracing member welded to a rectangular hollow section chord member. A set of joint failure modes are established for gapped and overlapped bracings and the research is aimed towards establishing the yield and ultimate loads of such joints with the yield line method as the main analytical tool. The results of 150 joint tests, conducted both in isolation and in complete trusses at testing centres in three different countries, have been used to verify the theories proposed.